Comparison Study of Beryllium and Lithium Target System for Beam Shaping Assembly Used in Boron Neutron Capture Therapy - Harendza, David; Trihandaru, Suryasatriya; Santosa, Slamet; Sardjono, Yohanes (Universitas Muhammadiyah Surakarta, 2015)
Boron neutron capture therapy (BNCT) is a selective targeting cancer therapy method which is by radiating epithermal neutron beams to a tumor which has been injected by boron-10 compound. The implementation of this method requires 2 (two) key elements, namely the boron-10 compound and the irradiating neutron beam of epithermal energy level. The neutron source used in this research was 13 MeV 1mA cyclotrons which have been developed by Indonesia National Nuclear Energy Agency. This paper was preoccupied in beam shaping assembly (BSA) target system. BSA target system is used to convert the proton produced by cyclotron into neutron. IAEA generated a recommendation for BNCT neutron beam quality, one of them was epithermal neutron flux which is higher than 109